Prospective EFL teachers’ perception toward teaching English vocabulary through poetry - Suwastini, Ni Komang Arie; Rahmayanti, Putu (Universitas Muhammadiyah Sidoarjo, 2024)
Poetry has been reported to promote language awareness and authentic learning sources. As poems are composed in carefully arranged words to form rhyming sounds with beautiful rhythm, the present study aimed to reveal EFL students' perceptions of using poetry to teach English vocabulary. As a qualitative research, the present study observed eighty-seven short essays on using English poems for improving students' vocabulary written by students in an English Language Education Department in Bali. It was revealed that the student-teachers perceived poetry to help improve students' acquisition of word form, use, and meaning. Forty-four students wrote poems that could improve students' understanding of English word forms; twenty-three students argued that poetry could improve students' pronunciation. Twenty-one participants believed poems could improve students' spelling. In terms of word meaning, a total of thirty vouched for the use of poetry for introducing figurative languages (twenty-three students), enhancing students' acquisition of colloquial vocabulary (eleven students), and familiarizing students with unfamiliar words (eleven participants). Nine students insisted that poems could be used to improve students' word use, whereas six students believed poems could display grammatical functions. At the same time, three participants recognized the use of poems for acquainting students with collocations. These results imply that future EFL teachers recognize the potential of bringing English poetry as a medium for improving their EFL students'' vocabulary, hinting at the need for further research on the systematic procedure of how to implement poetry into EFL classrooms. HIGHLIGHTS : Poetry, incorporating rhyme, figurative language, and diction, enables students to learncreative vocabulary through pronunciation, spelling, figurative language, colloquiallanguage, unfamiliar words, grammatical function, and collocation. Poetry comes in form of short and rich texts providing contextual sources for vocabularyelements. Hence, it can enhance vocabulary learning through engaging activities, butteachers must consider students' level and type. Vocabulary enhances students' receptive and productive skills, particularly writing.Poetry in EFL classes can enhance comprehension and consumption of complex texts,supporting the writing process and improving eloquence, ultimately affecting the qualityof writing results.